Modified fast-charging graphite negative electrode material and modification method and application thereof
By pretreating graphite raw materials and liquid-phase composite treatment of bacterial residue extract and bamboo source extract, a modified fast-charge graphite negative electrode material was prepared, which solved the problem of unsatisfactory fast charging performance of graphite negative electrode and significantly improved the charging efficiency and safety of lithium-ion batteries.
Patent Information
- Application Number
- CN202211631397.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The fast charging performance of graphite negative electrodes in lithium-ion batteries is not ideal, resulting in low charging efficiency and safety risks.
By pretreating the graphite raw material in an atmosphere containing carbon dioxide, then liquid composited with bacterial residue extract and bamboo source extract, and finally carbonized in a protective atmosphere, a modified fast-charge graphite negative electrode material was prepared.
It improves the kinetic energy of lithium ions, enhances the transmission channels and pathways of lithium ions, and significantly improves the fast charging performance and cycle stability of graphite negative electrodes.
Smart Images

Figure BDA0004005933850000081 
Figure BDA0004005933850000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials, and specifically relates to a new field of graphite modification. Background Art
[0002] In 2021, my country's electric vehicle sales reached 3.5 million, with a penetration rate of 13%. In order to further increase the popularity of electric vehicles, improving the battery charging rate is one of the most important issues to be solved. This is because compared with the efficiency of fuel vehicles that can be filled with fuel in a few minutes, the charging of electric vehicles is still very inefficient, which is also one of the bottlenecks for the further development of lithium-ion batteries.
[0003] When the battery is charging, lithium ions are extracted from the positive electrode and embedded in the graphite negative electrode. Since lithium ions can only be inserted from the interlayer when the graphite negative electrode is embedded with lithium, that is, the lithium embedding is directional, the embedding rate of lithium ions is inherently slow. Moreover, when the lithium embedding rate is accelerated, the overpotential of the graphite surface will increase, causing the actual voltage to be lower than the lithium deposition voltage, resulting in the precipitation of lithium metal or even lithium dendrites on the graphite surface. Especially at the sharp angles of the graphite surface, the lithium deposition phenomenon is more serious, and the precipitated lithium may grow into dendrites, which will pierce the diaphragm and cause a short circuit between the positive and negative electrodes. Therefore, the graphite negative electrode generally cannot allow lithium ions to be embedded too quickly, and from a safety perspective, lithium ions are not allowed to be embedded quickly. That is, fast charging performance is one of the bottleneck problems of the graphite negative electrode. Summary of the invention
[0004] In view of the problem that the fast charging performance of graphite materials is not ideal, the first purpose of the present invention is to provide a treatment method for improving the fast charging performance of graphite negative electrodes, aiming to provide a modification method that can improve the fast charging ability of graphite.
[0005] The second purpose of the present invention is to provide a modified fast-charging graphite negative electrode material prepared by the treatment method and its application in lithium secondary batteries.
[0006] The third object of the present invention is to provide a lithium secondary battery and a positive electrode thereof comprising the modified fast-charging graphite negative electrode material.
[0007] A method for improving the fast charging performance of a graphite negative electrode, comprising:
[0008] Step (1):
[0009] Pre-treating the graphite raw material in an atmosphere containing carbon dioxide at a temperature of 900 to 1200° C. to obtain pre-treated graphite;
[0010] Step (2):
[0011] The pretreated graphite is compounded with the fungus residue extract and the bamboo source extract in liquid phase to obtain modified graphite;
[0012] The fungus residue extract is a liquid extract obtained by solvothermal treatment of the fungus residue in a composite solvent containing alkali and water and then solid-liquid separation;
[0013] The bamboo extract is a liquid extract obtained by hydrothermally treating the bamboo in an alkali solution and then separating the bamboo from the solid and liquid;
[0014] Step (3):
[0015] The modified graphite and the carbon source are compounded and then carbonized in a protective atmosphere at a temperature of 700-900°C to obtain a modified fast-charging graphite negative electrode material.
[0016] In response to the problem of unsatisfactory fast-charging performance of graphite, the present invention innovatively pre-treats the graphite in an atmosphere containing carbon dioxide, and then combines it with a modification treatment of mushroom residue extract and bamboo source extract. This can achieve synergy, improve the adaptability of lithium ions, improve the storage, embedding and de-embedding kinetic energy of lithium ions, improve the transmission channels and pathways of lithium ions, and thus synergistically improve its fast-charging performance.
[0017] In the present invention, the graphite raw material can be any material that theoretically requires fast-charging modification, for example, it can be at least one of artificial graphite, natural graphite, and waste graphite recycling material;
[0018] In the present invention, the pretreatment under the carbon dioxide atmosphere and the subsequent combined modification of the fungus residue extract and the bamboo source extract are the key to synergistically improving the fast charging performance of graphite.
[0019] Preferably, the atmosphere containing carbon dioxide is pure carbon dioxide or a mixture of carbon dioxide and protective gas;
[0020] Preferably, the volume content of carbon dioxide in the atmosphere is greater than or equal to 20%; preferably 50-95% by volume;
[0021] Preferably, the temperature in the pretreatment stage is 950-1000°C.
[0022] Preferably, the pretreatment time is 2 to 15 hours, more preferably 4 to 10 hours.
[0023] In the present invention, the combination of the mushroom residue extract and the bamboo source extract is another key to synergistically improving the fast charging performance of graphite. The present invention also found that further control of the method for obtaining each extract can help further achieve complementary advantages and help further synergistically improve the fast charging performance of graphite.
[0024] The bacterial residue is antibiotic bacterial residue;
[0025] Preferably, the alkali is at least one of sodium hydroxide and potassium hydroxide;
[0026] Preferably, in the composite solvent, the concentration of the base is 0.1 to 2 M, more preferably 0.5 to 1.5 M;
[0027] Preferably, the solvent thermal starting composite solvent also contains alcohol; preferably, the alcohol is an alcohol miscible with water, preferably a C1-C4 alcohol, and more preferably ethanol; the present invention has found that further adding alcohol to the solvent thermal system helps to further coordinate with other processes and helps to further improve the performance of the prepared material.
[0028] Preferably, in the composite solvent, the volume ratio of alcohol to water is 0.1-10:1; preferably 1-2:1-2;
[0029] Preferably, the weight-to-volume ratio of the fungus residue to the composite solvent is 5 to 20 ml / g, preferably 10 to 18 ml / g;
[0030] Preferably, the solvent heat temperature is 180-250°C, preferably 200-220°C;
[0031] Preferably, the solvent thermal time is 5 to 10 hours.
[0032] The bamboo source is at least one of bamboo nodes and bamboo leaves;
[0033] Preferably, the alkali solution is an aqueous solution of at least one of sodium hydroxide and potassium hydroxide;
[0034] Preferably, the solute concentration of the alkali solution is 0.5 to 2 M;
[0035] Preferably, the weight-to-volume ratio of the bamboo source to the alkali solution is 5 to 20 ml / g, preferably 10 to 18 ml / g;
[0036] Preferably, the hydrothermal temperature is 180-250°C, preferably 200-220°C;
[0037] Preferably, the hydrothermal time is 2 to 15 hours, preferably 5 to 12 hours.
[0038] In step (2), the pretreated graphite is immersed in a mixed solution containing a solution of a fungus residue extract and a bamboo extract; or, it is immersed in a solution of a fungus residue extract and a solution of a bamboo extract respectively to obtain the modified graphite.
[0039] Preferably, the pretreated graphite is alternately impregnated in a solution of a fungus residue extract and a solution of a bamboo extract in any order to obtain the modified graphite. The present invention has found that under the synergistic innovation of the pretreatment and the fungus residue extract and the bamboo extract, the alternating impregnation modification process can unexpectedly further facilitate the construction of a longitudinal transmission path, which helps to further synergistically improve the fast charging performance of graphite.
[0040] Further preferably, the pretreated graphite is impregnated alternately in the order of first impregnation with a solution of the fungus residue extract and then with a solution of the bamboo source extract to obtain the modified graphite. The present invention further studies and finds that under the pre-modification by alternating impregnation with the fungus residue extract or the bamboo source extract, a synergistic longitudinal transmission path can be further constructed, which helps to further improve the fast charging performance.
[0041] Preferably, the total immersion time is 2 to 20 hours;
[0042] Preferably, in the alternating dipping stage, the number of alternating dipping is 2 to 5 times;
[0043] Preferably, the time of each impregnation in the alternating impregnation stage is 0.5 to 2 hours.
[0044] In the present invention, the carbon source has no special requirements and can be a conventional organic material with a certain bonding ability. For example, the carbon source is at least one of asphalt, resin, glucose, and dopamine.
[0045] Preferably, the weight ratio of the modified graphite to the carbon source is 1:0.01-0.1, preferably 1:0.01-0.05;
[0046] Preferably, the protective atmosphere is at least one of nitrogen and inert gas;
[0047] Preferably, the carbonization time is 3 to 10 hours.
[0048] The present invention provides a preferred treatment method for improving the fast charging performance of graphite negative electrode. The specific implementation steps are:
[0049] ① Pre-treat the finished graphite powder, wherein the pre-treatment temperature is 900-1200° C., the time is 2-10 hours, the atmosphere is a mixture of carbon dioxide and argon, and the volume proportion of carbon dioxide is 50-95%.
[0050] ② Prepare two precursor solutions. Solution 1: Place the fungus residue in an alcohol-alkali aqueous solution, then place it in a reactor at 200-220°C for 5-10 hours. Solution 2: Place the bamboo leaf powder in an alkaline solution with a solid-liquid ratio of 6-18:1, then place it in a reactor at 200-220°C for 2-15 hours.
[0051] ③ Soak the pretreated graphite powder alternately in the precursor solution 1 and the solution 2. The number of alternate soaking times is 2 to 5 times.
[0052] ④ Mix the soaked graphite with 2.5-4% asphalt powder, and then perform a second high-temperature treatment at 700-900°C for 3-10 hours in a nitrogen atmosphere.
[0053] The present invention also includes a modified fast-charging graphite negative electrode material prepared by the treatment method.
[0054] The modification method described in the present invention can impart special microscopic properties to the material and can improve the fast charging performance.
[0055] The present invention also provides an application of the modified fast-charging graphite negative electrode material, which is used to prepare a lithium secondary battery;
[0056] Preferably, it is used to prepare the negative electrode of a lithium secondary battery;
[0057] Preferably, the lithium secondary battery is a lithium ion battery.
[0058] The present invention also provides a lithium secondary battery negative electrode, comprising a current collector and a negative electrode material composited on the surface of the current collector, wherein the negative electrode material contains the modified fast-charging graphite negative electrode material.
[0059] The present invention also provides a lithium secondary battery, comprising the negative electrode of the present invention.
[0060] The modified negative electrode active material of the present invention can be used to prepare the required lithium secondary battery and its positive electrode and positive electrode material based on existing means.
[0061] Beneficial effects:
[0062] The present invention innovatively pretreats graphite in an atmosphere containing carbon dioxide, and then performs a joint modification treatment with fungus residue extract and bamboo source extract liquid. This can achieve synergy, improve the adaptability of lithium ions, improve the storage, embedding and de-embedding kinetic energy of lithium ions, improve the transmission channels and pathways of lithium ions, and thus synergistically improve its fast charging performance.
[0063] In addition, in the present invention, the alternating compounding method of first adding the fungus residue extract and then the bamboo source extract is adopted, which helps to further synergistically improve the fast charging performance of the prepared material. DETAILED DESCRIPTION
[0064] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited thereto.
[0065] In the following cases, the bacterial residues may be bacterial residues mixed with antibiotics produced by conventional pharmaceutical factories, which mainly contain calcium oxalate, residual protein, culture medium, etc. The graphite powder may be commercial artificial graphite powder.
[0066] Example 1
[0067] ① The graphite powder is subjected to the first step of high-temperature heat treatment, the heat treatment temperature is 950°C, the time is 10 hours, the atmosphere is a mixture of carbon dioxide and argon, and the volume proportion of carbon dioxide is 90%.
[0068] ②Prepare two precursor solutions.
[0069] Solution 1 is antibiotic bacterial residue treated by alkaline alcohol thermal method. 1 mol / L sodium hydroxide solution and an equal volume of anhydrous ethanol are mixed to prepare a composite solution (solution A), and the antibiotic bacterial residue is dissolved in the solution with a liquid-to-solid volume weight ratio of 18:1 ml / g, and then placed in a pressure-resistant reactor for solvent thermal treatment at 200°C for 7 hours, followed by solid-liquid separation to obtain solution 1.
[0070] Solution 2 is bamboo leaf powder treated by alkaline hydrothermal method. That is, 1 mol / L sodium hydroxide solution (solution B) dissolved in water is prepared, bamboo leaf powder is dissolved in the solution, the liquid-solid volume weight ratio is 16:1 ml / g, and then put into a pressure-resistant reactor for hydrothermal treatment at 200°C for 12 hours, followed by solid-liquid separation to obtain solution 2.
[0071] ③ Soak the pretreated graphite powder in solution 1 and then solution 2 in sequence, wherein the single solution is soaked and then dried before soaking in the subsequent solution, and the soaking time of the single solution is 1 hour. The number of alternating soakings is 5 times.
[0072] ④ The soaked graphite and asphalt powder (2.5wt.% of the weight of the graphite in step ③) were mixed, and then subjected to a second high-temperature treatment at 750°C for 10 hours in a nitrogen atmosphere to obtain an active material.
[0073] Example 2
[0074] Compared with Example 1, the only difference is that the heat treatment temperature of ① is changed to:
[0075] Group A: heat treatment temperature is 1200℃;
[0076] Group B: heat treatment temperature is 1100℃;
[0077] Other operations and parameters are the same as in Example 1.
[0078] Example 3
[0079] Compared with Example 1, the only difference is that the composite process of ③ is changed to:
[0080] Group A: The collected solution 1 and solution 2 were mixed to obtain a mixed solution, and the pretreated graphite powder was immersed in the mixed solution. The single immersion time was 1 hour, and the immersion was repeated 5 times; other operations and parameters were the same as those in Example 1;
[0081] Group B: The pretreated graphite powder was alternately immersed in solution 2 and then solution 1. Other operations and parameters were the same as those in Example 1.
[0082] Example 4
[0083] Compared with Example 1, the only difference is that in ②, solution A lacks ethanol, and other operations and parameters are the same as in Example 1.
[0084] Example 5
[0085] ① The graphite powder is subjected to the first step of high-temperature heat treatment, the heat treatment temperature is 1050°C, the time is 6 hours, the atmosphere is a mixture of carbon dioxide and argon, and the volume proportion of carbon dioxide is 80%.
[0086] ②Prepare two precursor solutions.
[0087] Solution 1 is antibiotic bacterial residue treated by alkaline alcohol thermal method. 1.5 mol / L sodium hydroxide solution and an equal volume of anhydrous ethanol are mixed to prepare a composite solution, and the antibiotic bacterial residue is placed in the solution with a liquid-solid ratio of 14:1 ml / g, and then placed in a reactor for solvent thermal treatment at 210°C for 5 hours, followed by solid-liquid separation to obtain solution 1.
[0088] Solution 2 is bamboo leaf powder treated by alkaline hydrothermal method. That is, 1.5 mol / L sodium hydroxide solution dissolved in water is prepared, bamboo leaf powder is placed in the solution, the liquid-solid ratio is 12:1 ml / g, and hydrothermally treated at 200°C for 9 hours, followed by solid-liquid separation to obtain solution 2.
[0089] ③ The pretreated graphite powder was alternately immersed in the precursor solution 1 and the solution 2, wherein the single solution was immersed and then dried before being immersed in the subsequent solution, and the single solution immersion time was 2 hours. The number of alternate immersions was 4 times.
[0090] ④ Mix the soaked graphite and asphalt powder (3.5wt.% of the weight of the graphite in step ③), and then perform a second high-temperature treatment at 800°C for 7 hours in a nitrogen atmosphere.
[0091] Example 6
[0092] ① The graphite powder is subjected to the first step of high-temperature heat treatment, the heat treatment temperature is 1100°C, the time is 4 hours, the atmosphere is a mixture of carbon dioxide and argon, and the volume proportion of carbon dioxide is 60%.
[0093] ②Prepare two precursor solutions.
[0094] Solution 1 is antibiotic bacterial residue treated by alkaline alcohol thermal method. 0.5 mol / L sodium hydroxide solution and an equal volume of anhydrous ethanol are mixed to prepare a composite solution, and the antibiotic bacterial residue is placed in the solution with a liquid-solid ratio of 10:1 ml / g, and then placed in a reactor for solvent thermal treatment at 220°C for 5 hours, followed by solid-liquid separation to obtain solution 1.
[0095] Solution 2 is bamboo leaf powder treated by alkaline hydrothermal method. That is, 0.5 mol / L sodium hydroxide solution dissolved in water is prepared, bamboo leaf powder is dissolved in the solution, the liquid-solid ratio is 8:1 ml / g, and then put into a reactor for hydrothermal treatment at 220°C for 5 hours, followed by solid-liquid separation to obtain solution 2.
[0096] ③Alternately immerse the pretreated graphite powder into the precursor solution 1 and solution 2. After immersing in a single solution, dry it and then immerse it in the subsequent solution. The immersion time of the single solution is 3 hours. The number of alternating immersions is 3 times.
[0097] ④ Mix the soaked graphite with asphalt powder (3.5wt.% of the weight of the graphite in step ③), and then perform a second high-temperature treatment at 900°C for 4 hours in a nitrogen atmosphere.
[0098] Comparative Example 1
[0099] Compared with Example 1, the only difference is that ① high temperature treatment is not performed, and the graphite powder is directly subjected to ② and subsequent steps, and the parameters are the same as in Example 1.
[0100] Comparative Example 2
[0101] Compared with Example 1, the only difference is that ① the high-temperature treatment atmosphere is pure argon, and the other processes and parameters are the same as Example 1.
[0102] Comparative Example 3
[0103] Compared with Example 1, the only difference is that in ③, only solution 1 is used for immersion treatment, and the immersion time is 10 hours. Other operations and parameters are the same as in Example 1.
[0104] Comparative Example 4
[0105] Compared with Example 1, the only difference is that in ③, only the solution 2 is immersed for 10 hours. Other operations and parameters are the same as in Example 1.
[0106] Comparative Example 5
[0107] Compared with Example 1, the only difference is that the processing temperature of ① is 800°C, and the other operations and parameters are the same as Example 1.
[0108] Comparative Example 6
[0109] Compared with Example 1, the only difference is that the processing temperature of ① is 1300°C, and the other operations and parameters are the same as Example 1.
[0110] Comparative Example 7
[0111] Compared with Example 1, the only difference is that in ①, the graphite powder is placed in a 10-20% hydrogen peroxide solution and stirred for 2 hours, and then the subsequent steps are carried out.
[0112] Comparative Example 8
[0113] Compared with Example 1, the only difference is that in ②, solution B is 1M sulfuric acid solution, and other operations and parameters are the same as in Example 1.
[0114] Performance Testing
[0115] The electrode materials prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 8 are made into electrode slurries. The slurry ratio is electrode material: binder (PAA): conductive agent (SP) = 75:15:10. After the slurry is stirred evenly, it is coated on a copper foil and then dried under vacuum. The dried electrode sheet is used as the working electrode of the button battery, the lithium sheet is used as the counter electrode, and the electrolyte is 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) electrolyte in a volume ratio of 1:1. The first lithium delithiation capacity of the above-mentioned material is tested at a current density of 0.5C, and its capacity is continued to be tested at a current of 10C, and the ratio of the capacity at 10C and 0.5C is used as an indicator of its rapid charge and discharge performance. The constant current charge and discharge voltage range is 0.01~1.5V. In addition, it is further cycled for 200 times at 40°C, and the capacity retention rate is recorded. The results are shown in Table 1:
[0116] Table 1: Test results of examples and comparative examples
[0117]
[0118]
[0119] It can be seen from Table 1 that the method of the present invention can be used to effectively modify graphite, and its fast charging performance and cycle stability can be improved. In addition, further adopting an alternating modification method of first solution one and then solution two can further synergistically improve the fast charging performance of the material.
Claims
1. A method for improving the fast charging performance of a graphite negative electrode, characterized in that the steps include: Step (1): The graphite raw material is pretreated in an atmosphere containing carbon dioxide at a temperature of 900-1200° C. to obtain pretreated graphite; Step (2): The pretreated graphite is immersed in a mixed solution containing a solution of a fungus residue extract and a bamboo-derived extract; or, the pretreated graphite is immersed in a solution of a fungus residue extract and a solution of a bamboo-derived extract respectively to obtain modified graphite; the fungus residue is antibiotic fungus residue; The fungus residue extract is a liquid extract obtained by solvothermal treatment of the fungus residue in a composite solvent containing alkali and water and then solid-liquid separation; The bamboo extract is a liquid extract obtained by hydrothermally treating the bamboo in an alkali solution and then separating the bamboo from the solid and liquid; Step (3): The modified graphite and the carbon source are compounded and then carbonized in a protective atmosphere at a temperature of 700-900°C to obtain a modified fast-charging graphite negative electrode material; the carbon source is an organic material.
2. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The graphite raw material is at least one of artificial graphite, natural graphite and recycled waste graphite.
3. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The atmosphere containing carbon dioxide is pure carbon dioxide or a mixture of carbon dioxide and protective gas.
4. The method for improving the fast charging performance of a graphite negative electrode according to claim 3, characterized in that: In the atmosphere, the volume content of carbon dioxide is greater than or equal to 20%.
5. The method for improving the fast charging performance of a graphite negative electrode according to claim 4, characterized in that: In the atmosphere, the volume content of carbon dioxide is 50-95v%.
6. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The pretreatment time is 2~15h.
7. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The alkali is at least one of sodium hydroxide and potassium hydroxide.
8. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: In the composite solvent, the concentration of the base is 0.1-2M.
9. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The initial complex solvent of the solvothermal reaction also contains alcohol.
10. The method for improving the fast charging performance of a graphite negative electrode according to claim 9, characterized in that: The alcohol is miscible with water.
11. The method for improving the fast charging performance of a graphite negative electrode according to claim 10, characterized in that: The alcohol is ethanol.
12. The method for improving the fast charging performance of a graphite negative electrode according to claim 9, characterized in that: In the composite solvent, the volume ratio of alcohol to water is 0.1-10:
1.
13. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The weight-to-volume ratio of the fungus residue and the composite solvent is 5-20 ml / g.
14. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The solvent heat temperature is 180-250°C.
15. The method for improving the fast charging performance of a graphite negative electrode according to claim 14, characterized in that: The solvent heat temperature is 200-220°C.
16. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The solvent thermal time is 5~10h.
17. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The bamboo source is at least one of bamboo nodes and bamboo leaves.
18. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The alkali solution is an aqueous solution of at least one of sodium hydroxide and potassium hydroxide.
19. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The solute concentration of the alkali solution is 0.5~2M.
20. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The weight volume ratio of bamboo source and alkali solution is 5~20ml / g.
21. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The hydrothermal temperature is 180~250℃.
22. The method for improving the fast charging performance of a graphite negative electrode according to claim 21, characterized in that: The hydrothermal temperature is 200~220℃.
23. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The hydrothermal time is 2~15h.
24. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The pretreated graphite is alternately immersed in a solution of a fungus residue extract and a solution of a bamboo source extract in any order to obtain the modified graphite.
25. The method for improving the fast charging performance of a graphite negative electrode according to claim 24, characterized in that: The pretreated graphite is impregnated alternately in the order of first the solution of the fungus residue extract and then the solution of the bamboo source extract to obtain the modified graphite.
26. The method for improving the fast charging performance of a graphite negative electrode according to claim 24, characterized in that: The total immersion time is 2 to 20 hours.
27. The method for improving the fast charging performance of a graphite negative electrode according to claim 24, characterized in that: In the alternating dipping stage, the number of alternating dipping is 2 to 5 times.
28. The method for improving the fast charging performance of a graphite negative electrode according to claim 27, characterized in that: The time of each immersion in the alternating immersion stage is 0.5~2h.
29. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The carbon source is at least one of asphalt, resin, glucose and dopamine.
30. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The weight ratio of the modified graphite to the carbon source is 1:0.01-0.
1.
31. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The protective atmosphere is at least one of nitrogen and inert gas.
32. The method for improving the fast charging performance of a graphite negative electrode according to claim 1, characterized in that: The carbonization time is 3~10h.
33. A modified fast-charging graphite negative electrode material prepared by the treatment method according to any one of claims 1 to 32.
34. An application of the modified fast-charging graphite negative electrode material according to claim 33, characterized in that: It is used to prepare lithium secondary batteries.
35. The use of the modified fast-charging graphite negative electrode material as claimed in claim 34, characterized in that: It is used to prepare the negative electrode of lithium secondary battery.
36. The use of the modified fast-charging graphite negative electrode material as claimed in claim 35, characterized in that: The lithium secondary battery is a lithium ion battery.
37. A negative electrode for a lithium secondary battery, comprising a current collector and a negative electrode material composited on the surface thereof, characterized in that: The negative electrode material includes the modified fast-charging graphite negative electrode material described in claim 33.
38. A lithium secondary battery, characterized in that: Comprising the negative electrode as described in claim 37.
Citation Information
Patent Citations
Method for preparing thin-layer graphene negative electrode active material by utilizing antibiotic bacterium dregs
CN112225203A
Heterogeneous carbon coated graphite negative electrode material, preparation thereof and application of graphite negative electrode material in lithium secondary battery
CN113839039A